2012
DOI: 10.1111/j.1442-9071.2012.02844.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic revision for failed primary external versus endoscopic dacryocystorhinostomy

Abstract: The success rate of revisional dacryocystorhinostomy in the previous external dacryocystorhinostomy group was slightly higher than that in the previous endoscopic dacryocystorhinostomy group. Differences in preoperative and perioperative endoscopic findings were detected between the groups. Clarifying these differences in endoscopic revision will help improve the surgical outcomes of primary surgery involving either external or endoscopic dacryocystorhinostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 14 publications
3
31
1
1
Order By: Relevance
“…12 Interestingly, significantly more inappropriately sized or posi tioned ostium were found following previous endonasal DCR. Our study did not find this association with ostium size or position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Interestingly, significantly more inappropriately sized or posi tioned ostium were found following previous endonasal DCR. Our study did not find this association with ostium size or position.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported success rates in adults for REEDCR range from 60% to 94% (Table 2). [8][9][10][11][12][13][14][15][16][17][18] The out come measures used vary widely, and not all studies reported both anatomical and functional success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported success rates of endoscopic revision surgery ranged from 60% to 94% [7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Так, например, имеются данные, согласно которым процент недостаточно эффек-тивных оперативных вмешательств составляет 5-16 % при наружном доступе и до 40 % при эндоскопическом [10,11]. Существуют также данные ретроспективного исследования 77 па-циентов, подвергшихся ревизионной ДЦРС, в результате которого также выяснилось, что успешность эндоскопической дакриоцисторино-стомии несколько меньше (80,7 %), чем наружной (84 %) [13].…”
Section: результаты и их обсуждениеunclassified